Preparing future teachers of elementary school to monitor the quality of education - Митник, Олександр Якович (Educological discourse, 2013)
The article disclosed the content of training future teachers of elementary school to master the technology development and evaluation of various tests in mathematics, Ukrainian language. Filed development seminars course “Teaching Methods in the field of education in Mathematics”, dedicated to training students prepare and evaluate differentiated by the level of complexity mathematic tests.